2016
DOI: 10.1097/sle.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prophylactic Antiemetic Efficacy of Aprepitant Plus Palonosetron Versus Aprepitant Plus Ramosetron in Patients at High Risk for Postoperative Nausea and Vomiting After Laparoscopic Cholecystectomy: A Prospective Randomized-controlled Trial

Abstract: We compared the antiemetic efficacy of aprepitant plus palonosetron versus aprepitant plus ramosetron in patients after laparoscopic cholecystectomy. A total of 88, nonsmoking, female patients undergoing laparoscopic cholecystectomy were randomly allocated to 2 groups of 44 each who received palonosetron 0.075 mg (aprepitant plus palonosetron group) and ramosetron 0.3 mg (aprepitant plus ramosetron group) after induction of anesthesia. All patients received aprepitant 80 mg 2 hours before surgery. The incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Two were excluded as aprepitant was not being compared with other antiemetics in those studies. [ 24 25 ] One was found to be an abstract of another full text article[ 26 ] and hence excluded. Finally, seven articles on aprepitant were included for our systematic review [ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two were excluded as aprepitant was not being compared with other antiemetics in those studies. [ 24 25 ] One was found to be an abstract of another full text article[ 26 ] and hence excluded. Finally, seven articles on aprepitant were included for our systematic review [ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mixed results have been observed in clinical studies of other aprepitant two‐drug combinations for PONV prophylaxis (Table 3). For example, in a randomized, double‐blind study ( N = 88) in high‐risk patients undergoing cholecystectomy, Choi and colleagues observed that oral aprepitant 80 mg 2 h before surgery combined with the 5‐HT3 antagonist palonosetron 0.075 mg intravenously, compared with aprepitant 80 mg combined with the 5‐HT3 antagonist ramosetron 0.3 mg intravenously, significantly reduced the incidence of nausea (but not vomiting) at 0–2 h after surgery (13.6% vs. 36.4%; p = 0.014), 0–24 h after surgery (27.3% vs. 63.6%; p = 0.001), and 2–24 h after surgery (22.7% vs. 54.5%; p = 0.002) 48 . However, in a randomized, single‐blind study ( N = 100), Yoo and colleagues found no significant benefit in the reduction of PONV 24 h following elective surgery with preoperative oral aprepitant 80 mg combined with intravenous palonosetron 0.075 mg versus palonosetron 0.075 mg alone 49 .…”
Section: Efficacy Of Nk1ras Investigated For Ponv Prophylaxismentioning
confidence: 94%
“…For example, in a randomized, double-blind study (N = 88) in highrisk patients undergoing cholecystectomy, Choi and colleagues observed that oral aprepitant 80 mg 2 h before surgery combined with the 5-HT3 antagonist palonosetron 0.075 mg intravenously, compared with aprepitant 80 mg combined with the 5-HT3 antagonist ramosetron 0.3 mg intravenously, significantly reduced the incidence of nausea (but not vomiting) at 0-2 h after surgery (13.6% vs. 36.4%; p = 0.014), 0-24 h after surgery (27.3% vs. 63.6%; p = 0.001), and 2-24 h after surgery (22.7% vs. 54.5%; p = 0.002). 48 However, in a randomized, single-blind study (N = 100), Yoo and colleagues found no significant benefit in the reduction of PONV 24 h following elective surgery with preoperative oral aprepitant 80 mg combined with intravenous palonosetron 0.075 mg versus palonosetron 0.075 mg alone. 49 In a second randomized study (N = 84) in high-risk patients who had gynecologic surgery, oral aprepitant 80 mg combined with intravenous ramosetron 0.3 mg administered 2-3 h before surgery, compared with ramosetron alone, significantly reduced the incidence of vomiting at 24 h (80.9% vs. 52.4%; p < 0.05) and the use of rescue antiemetics.…”
Section: Aprepitant (Oral Emend)mentioning
confidence: 98%